PENANAMAN KETERAMPILAN KEWARGANEGARAAN MELALUI ORGANISASI SISWA INTRA SEKOLAH SMA TAMAN MULIA KUBU RAYA - Martina Merri; Agus Sastrawan; Bambang Budi Utomo (Universitas Tanjungpura, 2020)
AbstractThe study is titled Cultivating Citizenship Skills Through Intra-High School Student Organizations Taman Mulia Kubu Raya High School qualitative research method. Data collection techniques using observation, interviews, and study documentation. Research result. Strategies for inculcating citizenship skills in student council activities at Taman Mulia Kuburaya High School. The strategy of implementing citizenship skills in student council activities at Taman Mulia Kuburaya High School, gives an example first, The teacher is not just concerned with academic values, but appreciates the efforts of students by giving awards and good grades to students who are responsible for the assignments, as well as giving sanctions to reprimand students when making mistakes without scolding them, teach students to obey school rules, instill the value of honesty in students, motivate responsible attitude embedded in students. Constraints faced by the Intra-School Student Organization (OSIS) in inculcating citizenship skills at Taman Mulia Kuburaya High School. The teacher instills responsibility in school by setting a good example, and providing direction to students that character education is important to support good personality in students such as going to school on time, obeying school rules, shaking hands when meeting older people, speak good manners.Keywords:, Citizenship skills, (Civic Skiils), Planting skills, Student Council.